Diet of autochthonous populations in Yakutia using isotopic, ethnographic, historical and archaeological data. (December 2019) - Romanova, Liubomira; Balter, Vincent; Simon, Laurent; Gerard, Patrice; Pokatilova, Nadejda; Crubezy, Eric
Highlights: The diet of Yakuts is reconstructed using isotopic, archaeological and historical data. The stable carbon and nitrogen isotope values suggest Yakuts had meat and fish based diet. Excavated tombs contain meat and dairy products, but do not attest for fish consumption. Yakuts have lighter carbon isotope values compared to foragers of the Baikal region. The diet of Yakut population varies depending on periods, regions and social status. Abstract: This article investigates, for the first time, the diet of the Yakut population between the 15th and 19th centuries AD. Analyses of the stable isotopes of carbon and nitrogen in human and animal bone collagen were used for the study. The stable isotope values were then compared through four historical periods, three geographical areas, sexes, and socio-economic groups determined by the presence or absence of artefacts in the excavated tombs. The results highlight the variety of dietary practices among the Yakuts. There are significant differences between the North, characterised mostly by the consumption of herbivores, the Viluy region, where fish had an important role, and Central Yakutia with a diversified diet. No differences were seen between the diets of men and women. The group of elites had a stable diet based on meat and milk consumption. Samples before 1700AD had δ15N values that were higher than samples from other periods, probably due to greater consumption of fish and foal meat. These data were compared with ethnographic, historical and archaeological information so as to better depict the diet of these past populations.